Relação da pressão arterial com a proteinúria em gatos idosos ou doentes renais crônicos - Freitas, Maria Natália de (2024)
Systemic arterial hypertension (SAH) is a common comorbidity in elderly cats with chronic kidney disease (CKD). Proteinuria is related to the prognosis of CKD cats and may be related to the magnitude of hypertension. This observational study sought to correlate oscillometric systolic blood pressure with proteinuria, and with other hematological and biochemical findings in elderly cats and chronic kidney disease. Three groups were analyzed: nineteen young adult cats, 1 to 6 years of age (G1), nineteen elderly cats, over 10 years of age (G2) and thirteen cats with chronic kidney disease (G3). In the comparison of mean creatinine values, urinary protein-tocreatinine ratio (UPC), systolic blood pressure and age between the groups, a statistically significant difference was observed in creatinine, UPC and density in the CKD group (G3) compared to the other groups. There was no correlation between systolic blood pressure, age and proteinuria in the elderly and chronic kidney disease groups. However, there was a correlation between renal injury variables and weight, body score, and total plasma proteins. The results corroborate the care of hypertension in elderly cats given the higher individual blood pressure values and the care of body score in CKD cats, even at an early stage.